Thermoset Polyester Resin Microplastics: Effects on Enzymatic Biomarkers and Toxicological Endpoint Responses of Eisenia fetida Earthworms - David Amaya-Vías; Gemma Albendín; Vanessa Aranda-Quirós; Rocío Rodríguez-Barroso; Dolores Coello; Juana María Arellano (Toxics)
Thermosets are plastic composite materials widely used in many industrial sectors of modern society with an increasing presence in the environment. The adverse effects of this material on environmental compartments and biota of thermosets are still unknown. In this work, we studied the potential effects of two thermoset polyester resin-derived microplastics (R930A-SP and R930A-DVE1) on the survival, behavior, morphological changes and subcellular damage of earthworms Eisenia fetida. The proposed experimental conditions simulated environmentally relevant concentrations, taking as a reference other related microplastics present in the environment. Thus, E. fetida specimens were exposed to five concentrations (100, 500, 1000, 1500 and 2000 mg resin per kg soil) of these two resins for 14 days. At concentrations and exposure times studied, no significant effects on growth, measured as weight loss, or on the enzyme biomarkers (cholinesterase, carboxylesterase and glutathione S-transferase) were observed. Similarly, no behavioral changes were detected in earthworms, and the survival rate was 100%. Likewise, no differences were observed between the different formulations of the polyester resins studied. However, this study could serve as a starting point for further studies with higher concentrations and/or exposure times, as well as in combination with other pollutants.